The Role of Finnish Comprehensive School Principals in Inclusive Education Practice - Dibessa, Samson (2021)
The increasing trends of diversities and special educational needs in the school highly demands the collaboration of the school community toward inclusive education. The principals are the ones who lead the school communities. Hence, in this process, the school principals play a crucial role. This study examines the Finnish principals’ role in leading inclusive education as well as, identifies how they are leading the school cultures, policies, and practice to support inclusive education. The Index of inclusion, which has three main dimensions (culture, policy, and practice), was used as the main theoretical framework. A qualitative research method was used. A semi structured interview was used to collect the primary data, and school policy documents from two schools were used as the secondary data. The interviews were conducted online using Zoom. A qualitative content analysis was used to analyse the data. Data was interpreted using the inductive data analysis approach. The coding was done manually, and the data was coded into main categories followed by sub-categories. The research findings show that principals have three major roles: administrative, managerial and leadership roles. In particular, leading school cultures, policies, and practices through the special education teams and guiding school communities are the main factors that assist the principals in achieving an inclusive education vision. Furthermore, professional learning communities have a significant impact for professional development since they assist the principals in the goal of inclusive education through structured teams that distribute leadership.